2020
DOI: 10.1093/cercor/bhaa073
|View full text |Cite
|
Sign up to set email alerts
|

Confidence in Decision-Making during Probabilistic Tactile Learning Related to Distinct Thalamo–Prefrontal Pathways

Abstract: The flexibility in adjusting the decision strategy from trial to trial is a prerequisite for learning in a probabilistic environment. Corresponding neural underpinnings remain largely unexplored. In the present study, 28 male humans were engaged in an associative learning task, in which they had to learn the changing probabilistic strengths of tactile sample stimuli. Combining functional magnetic resonance imaging with computational modeling, we show that an unchanged decision strategy over successively presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 62 publications
(72 reference statements)
0
18
0
Order By: Relevance
“…A key model assumption from the rodent work was that the MD thalamus performs an intermediate-level computation rather than a sensory signal relay [ 20 , 21 ]. We first confirmed that this is the case for the human brain, by examining fMRI data of human participants performing a probabilistic inference task [ 32 ]. We then asked the neural model to solve components of the same probabilistic inference task and identified a role for the MD in rapid and flexible gating of human dlPFC strategy representations.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…A key model assumption from the rodent work was that the MD thalamus performs an intermediate-level computation rather than a sensory signal relay [ 20 , 21 ]. We first confirmed that this is the case for the human brain, by examining fMRI data of human participants performing a probabilistic inference task [ 32 ]. We then asked the neural model to solve components of the same probabilistic inference task and identified a role for the MD in rapid and flexible gating of human dlPFC strategy representations.…”
Section: Introductionmentioning
confidence: 80%
“…To draw direct parallels between the neural model and human data, we returned to our previously collected dataset [ 32 ] and took a different analytical approach from the published work. In mice, prefrontal inhibition impaired overall performance, while MD inhibition led to impairment specifically when animals were required to switch behavior [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the learning mechanism that modifies these pathways is lacking. [21] showed similar functional connectivity in humans when looking at the activity of the thalamus, orbital frontal cortex, and the vmPFC during a tactile task. They found that when the subject switches strategy, both the thalamus and orbital frontal cortex are activated, while when the subject keeps the same strategy, both the thalamus and vmPFC area are activated.…”
Section: Introductionmentioning
confidence: 70%
“…The prefrontal cortex (PFC), and more specifically the orbitofrontal cortex (OFC), has long been implicated in the ability to respond adaptively and flexibly to obtain reward 4,5 . We recently identified the OFC in humans as a critical brain region related to updating the decision strategy based on newly accumulated evidence 6 . Recent studies emphasize that OFC supports value-guided behaviour by representing the predictions about specific outcomes associated with sensory stimuli 7,8 .…”
Section: Introductionmentioning
confidence: 99%